Clinical Utility of Urinary Cytology to Detect BK Viral Nephropathy. Issue 8 (August 2015) - Nankivell, Brian J.; Renthawa, Jasveen; Jeoffreys, Neisha; Kable, Kathy; O'Connell, Philip J.; Chapman, Jeremy R.; Wong, Germaine; Sharma, Raghwa N.
Abstract : Background: Reactivation of BK polyoma virus can result in destructive viral allograft nephropathy (BKVAN) with limited treatment options. Screening programs using surrogate markers of viral replication are important preventive strategies, guiding immunosuppression reduction. Methods: We prospectively evaluated the diagnostic test performance of urinary decoy cells and urinary SV40T immunochemistry of exfoliated cells, to screen for BKVAN, (defined by reference histology with SV40 immunohistochemistry, n = 704 samples), compared with quantitative viremia, from 211 kidney and 141 kidney-pancreas transplant recipients. Results: The disease prevalence of BKVAN was 2.6%. Decoy cells occurred in 95 of 704 (13.5%) samples, with a sensitivity of 66.7%, specificity of 88.6%, positive predictive value (PPV) of 11.7%, and negative predictive value of 98.5% to predict histologically proven BKVAN. Quantification of decoy cells improved the PPV to 32.1% (10 ≥ cells threshold). Immunohistochemical staining of urinary exfoliated cells for SV40T improved sensitivity to 85.7%, detecting atypical or degenerate infected cells (specificity of 92.3% and PPV of 33.3%), but was hampered by technical failures. Viremia occurred in 90 of 704 (12.8%) with sensitivity of 96.3%, specificity of 90.3%, PPV of 31.5%, and negative predictive value of 99.8%. The receiver-operator curve performance of quantitative viremia surpassed decoy cells (area under the curve of 0.95 and 0.79, respectively, P = 0.0018 for differences). Combining decoy cell and BK viremia in a diagnostic matrix improved prediction of BKVAN and diagnostic risk stratification, especially for high-level positive results. Conclusions: Although quantified decoy cells are acceptable surrogate markers of BK viral replication with unexceptional test performances, quantitative viremia displayed superior test characteristics and is suggested as the screening test of choice. Abstract : The authors conduct a randomized study to examine the effect of volatile anesthetics on acute graft injury and clinical outcomes after liver transplantation, which fails to show an additional beneficial effect of sevoflurane comparing to propofol. Supplemental digital content is available in the text.